Understanding health policy a clinical approach - Grumbach, Kevin; Bodenheimer, Thomas; McGraw-Hill's AccessMedicine (New York, N.Y. : McGraw-Hill Education LLC., 2012)
Expert practitioners in both the public and private healthcare sectors, the authors cover the entire scope of our healthcare system. From the concepts behind policy decisions to concrete examples of how they affect patients and professionals alike. Understanding Health Policy, 6e makes otherwise difficult concepts easy to understand.so you can make better decisions, improve outcomes, and enact positive change on a daily basis.
Chapter 1. Introduction: the paradox of excess and deprivation -- Chapter 2. Paying for health care -- Chapter 3. Access to health care -- Chapter 4. Reimbursing health care providers -- Chapter 5. How health care is organized i: primary, secondary, and tertiary care -- Chapter 6. How health care is organized ii: health delivery systems -- Chapter 7. The health care workforce and the education of health professionals -- Chapter 8. Painful versus painless cost control -- Chapter 9. Mechanisms for controlling costs -- Chapter 10. Quality of health care -- Chapter 11. Prevention of illness -- Chapter 12. Long-term care -- Chapter 13. Medical ethics and rationing of health care -- Chapter 14. Health care in four nations -- Chapter 15. Health care reform and national health insurance -- Chapter 16. Conflict and change in america's health care system -- Chapter 17. Conclusion: tensions and challenges -- Chapter 18. Questions and discussion topics.
"A Lange medical book."
"Previous editions copyright © 2005, 2002, 1998, 1995 by Appleton & Lange."
Includes bibliographical references and indexes.
Also issued in print and PDF version.
Description based on cover image and table of contents, viewed on May 12, 2014.
Keywords: Health Policy -- United States; Health Care Costs -- United States; Health Care Rationing -- United States; National Health Insurance, United States -- United States; Medical care -- United States; Medical policy -- United States; Electronic books